Psychological Well-Being of Patient with Confirmed Covid-19 at RSUP Dr. Mohammad Hoesin Palembang - Desti Elza Muslimah; Feriatmajaya (RSUP Dr Moh Hoesin Palembang, 2021)
Pandemic that occour at the end of 2019, Coronavirus Disease, caused respiratory tract infections with commonly till seriouslly symptoms. Patien confirmated with Covid-19 not only impact their somatic, but also their psychological and social condition. Untill now, Civil society still have negative assumed about Covid-19, which triggers social stigma and discrimination. Thats impacted to psychological well-being. Purpose of this reseach, described of psychological well being of patients with confirmed Covid-19 at RSUP Dr. Mohammad Hoesin Palembang 2021. Used quantitative descriptive design and total sample that took by purposive sampling was 45 samples. Analysis of the reseach used descriptive statistical percentage. The results describe the presentation of psychological well being was 4 respondents on high category of (8.8%), 40 respondents on moderate category 88.8%, and 1 respondent low category (2.20%). The highest score of psychological well-being in the moderate category is environment mastery dimension of 84.3%; in the high category is positive relation dimension of 26.6%; and in the low category is personal growth dimension of 15.6%. Expected of the reseach, to know overview of the psychological well-being of of patients with confirmed Covid-19 and make the optimally planning of the medical and non-medical care.